THE USE OF ROLE PLAYING TO IMPROVE SPEAKING ABILITY - Hartini Agustiawati (Global Expert: Jurnal Bahasa dan Sastra, 2018)
In Indonesia, students learn English as Foreign Language. It is not easy to do, but the use of English is very important to secure life. Students need English to search information, communicate and learn. There are many problems for teachers to teach English in the classroom, Such as low motivation, lazy to practice and a little time to teach.  Therefore, teachers need strategies to motivate and encourage students to learn, read and practice English. In order to help students to speak, a method can be used. Role Playing is a suitable method to develop students to talk. It motivates students to practice and show their performance in English.Key words: Speaking, Role Playing